Curriculum Reform and The Integration of Sustainable Development Education in English Language Classrooms - Davidson, Vincent Chukwujekwu; Maduegbunam, Theresa Obiageli; Okoro, Precious Ogonna (Universitas Jambi, Magister Program of English Education Department, 2026)
This study examined curriculum reform and the integration of Sustainable Development Education (SDE) in English language classrooms in secondary schools in Enugu State, Nigeria. The increasing need to align educational practices with global priorities, particularly the United Nations Sustainable Development Goal 4 (Quality Education), has heightened demand for curriculum innovations that promote sustainability awareness among students. The study investigated the extent to which sustainable development concepts are embedded in the English language curriculum and how teachers implement these concepts in classroom instruction. A descriptive survey research design was adopted. The population comprised English language teachers in public secondary schools in Enugu State. A sample was selected using a multistage sampling technique. Data were collected through a structured instrument titled the Curriculum Reform and Sustainable Development Education Integration Questionnaire (CRSDEIQ). Instrument validity was confirmed by experts in curriculum studies and English language education, while reliability was established using Cronbach’s alpha. Data were analyzed using mean, standard deviation, and t-test at the 0.05 level of significance to answer research questions and test hypotheses. Findings revealed that although elements of sustainable development education exist within the English language curriculum, classroom implementation remains limited. Major challenges identified included inadequate teacher training, insufficient instructional materials, and low teacher awareness of sustainability concepts. The study concluded that effective curriculum reform, supported by continuous professional development, is essential for promoting SDE through English language teaching. It recommended integrating sustainability-focused content into textbooks and providing targeted teacher training programmes to strengthen classroom implementation.